Epidemic Achromobacter xylosoxidans strain among Belgian cystic fibrosis patients and review of literature. Issue 1 (December 2016) - Cools, Piet; Ho, Erwin; Vranckx, Katleen; Schelstraete, Petra; Wurth, Bettina; Franckx, Hilde; Ieven, Greet; Van Simaey, Leen; Van daele, Sabine; Verhulst, Stijn; De Baets, Frans; Vaneechoutte, Mario
Abstract Background Achromobacter xylosoxidans is increasingly being recognized as an emerging pathogen in cystic fibrosis. Recent severe infections withA. xylosoxidans in some of our cystic fibrosis (CF) patients led to a re-evaluation of the epidemiology of CF-associatedA. xylosoxidans infections in two Belgian reference centres (Antwerp and Ghent). Several of these patients also stayed at the Rehabilitation Centre De Haan (RHC). In total, 59A. xylosoxidans isolates from 31 patients (including 26 CF patients), collected between 2001 and 2014, were studied. We evaluated Matrix Assisted Laser Desorption Ionisation -Time of Flight mass spectrometry (MALDI-TOF) as an alternative for McRAPD typing. Results Both typing approaches established the presence of a major cluster, comprising isolates, all from 21 CF patients, including from two patients sampled when staying at the RHC a decade ago. This major cluster was the same as the cluster established already a decade ago at the RHC. A minor cluster consisted of 13 isolates from miscellaneous origin. A further seven isolates, including one from a non-CF patient who had stayed recently at the RHC, were singletons. Conclusions Typing results of both methods were similar, indicating transmission of a single clone ofA. xylosoxidans among several CF patients from at least two reference centres. Isolates of the same clone were already observed at the RHC, a decade ago. It is difficult to establish to what extent the RHC is the source of transmission, because the epidemic strain was already present when the first epidemiological study in the RHC was carried out. This study also documents the applicability of MALDI-TOF for typing of strains within the speciesA. xylosoxidans and the need to use the dynamic cutoff algorithm of the BioNumerics® software for correct clustering of the fingerprints.